CLINICAL AND ORGANIZATIONAL ASPECTS OF SURGICAL CARE FOR VICTIMS WITH UNSTABLE PELVIC INJURIES IN POLYTRAUM - Burluka, V.V.; Tkachenko, O.A.; Мaksymenko, M.A.; Yakovenko, А.О. (World of Medicine and Biology, 2021)
The work is based on improving the results of treating victims with unstable pelvic injuries with polytrauma. An analysis of the treatment of 406 victims with unstable pelvic injuries with polytrauma (ISS≥17 points) is presented. In order to improve care for victims with severe and extremely severe combined pelvic injuries in the hospital, we used an improved protocol scheme of surgical treatment in victims of this group, which includes time intervals and corresponding priority actions taking into account the injury severity and traumatic disease prognosis. Active surgical tactics in the early and late periods of traumatic disease permitted to increase the number of internal metal osteosynthesis in this category of victims from 40.3 % to 72.06 %, to reduce the proportion of conservative treatment, which leads to significant disability of victims from 53.66 % to 30.61 %.
Keywords: combined trauma; fractures of the pelvis; traumatic disease; surgical tactics